Conditional ligands for Asian HLA variants facilitate the definition of CD8+ T‐cell responses in acute and chronic viral diseases. Issue 4 (14th February 2013) - Chang, Cynthia X. L.; Tan, Anthony T.; Or, Ming Yan; Toh, Kai Yee; Lim, Pei Yiing; Chia, Adeline S. E.; Froesig, Thomas M.; Nadua, Karen D.; Oh, Hsueh‐Ling J.; Leong, Hoe Nam; Hadrup, Sine R.; Gehring, Adam J.; et al.
<x xml:space="preserve">Abstract</x> Conditional ligands have enabled the high‐throughput production of human leukocyte antigen (HLA) libraries that present defined peptides. Immunomonitoring platforms typically concentrate on restriction elements associated with European ancestry, and such tools are scarce for Asian HLA variants. We report 30 novel irradiation‐sensitive ligands, specifically targeting South East Asian populations, which provide 93, 63, and 79% coverage for HLA‐A, ‐B, and ‐C, respectively. Unique ligands for all 16 HLA types were constructed to provide the desired soluble HLA product in sufficient yield. Peptide exchange was accomplished for all variants as demonstrated by an ELISA‐based MHC stability assay. HLA tetramers with redirected specificity could detect antigen‐specific CD8+ T‐cell responses against human cytomegalovirus, hepatitis B (HBV), dengue virus (DENV), and Epstein‐Barr virus (EBV) infections. The potential of this population‐centric HLA library was demonstrated with the characterization of seven novel T‐cell epitopes from severe acute respiratory syndrome coronavirus, HBV, and DENV. Posthoc analysis revealed that the majority of responses would be more readily identified by our unbiased discovery approach than through the application of state‐of‐the‐art epitope prediction. This flow cytometry‐based technology therefore holds considerable promise for monitoring clinically relevant antigen‐specific T‐cell responses in populations of distinct ethnicity.